(untitled) (Research, Society and Development, 2021)
The search for improvement in the quality of teaching is taken in several ways, and it is through these that we carry out surveys, studies, questioning of circumstances and analysis of the factors that affect school performance. The present study aims to survey the importance of high school in schools, as well as to problematize the crisis faced today in relation to school performance, and the great learning challenge in relation to the subjects of Portuguese and mathematics in high school, taking into account data and statistics about the importance of such content in school education. The methodology addressed in this research has a qualitative nature within an exploratory bibliographic perspective. The results identify that the difficulties presented by high school students, hinder and hinder their development during school education and also generate a negative result in the social and economic development of Brazil. Based on these results, the importance of agents who can modify this current reality experienced in the Brazilian scenario is discussed.